PFASs–restriction proposal commentary on ECHA’s Annex XV restriction report, proposal for a restriction, March 2023 - Klaus-Michael Wollin; Monika Batke; Georg Damm; Alexius Freyberger; Ursula Gundert-Remy; Aswin Mangerich; Jan G. Hengstler; Falko Partosch; Thomas Schupp; Anna Sonnenburg; Heidi Foth (Archives of Toxicology, 2023)

Quality of reporting animal studies - Monika Batke; Emanuela Corsini; Rex Fitzgerald; Eugenio Scanziani; Henri Schroeder; Inger-Lise Steffensen; Beate C. Ulbrich; Henk van Loveren; Dina Waalkens-Berendsen; Detlef Woelfle; Ursula Gundert-Remy (Archives of Toxicology, 2023)

Prediction of the dose range for adverse neurological effects of amiodarone in patients from an in vitro toxicity test by in vitro–in vivo extrapolation - Engi Abd el-Hady Algharably; Emma Di Consiglio; Emanuela Testai; Reinhold Kreutz; Ursula Gundert-Remy (Archives of Toxicology, 2021)
Amiodarone is an antiarrhythmic agent inducing adverse effects on the nervous system, among others. We applied physiologically based pharmacokinetic (PBPK) modeling combined with benchmark dose modeling to predict, based on published in vitro data, the in vivo dose of amiodarone which may lead to adverse neurological effects in patients. We performed in vitro–in vivo extrapolation (IVIVE) from concentrations measured in the cell lysate of a rat brain 3D cell model using a validated human PBPK model. Among the observed in vitro effects, inhibition of choline acetyl transferase (ChAT) was selected as a marker for neurotoxicity. By reverse dosimetry, we transformed the in vitro concentration–effect relationship into in vivo effective human doses, using the calculated in vitro area under the curve (AUC) of amiodarone as the pharmacokinetic metric. The upper benchmark dose (BMDU) was calculated and compared with clinical doses eliciting neurological adverse effects in patients. The AUCs in the in vitro brain cell culture after 14-day repeated dosing of nominal concentration equal to 1.25 and 2.5 µM amiodarone were 1.00 and 1.99 µg*h/mL, respectively. The BMDU was 385.4 mg for intravenous converted to 593 mg for oral application using the bioavailability factor of 0.65 as reported in the literature. The predicted dose compares well with neurotoxic doses in patients supporting the hypothesis that impaired ChAT activity may be related to the molecular/cellular mechanisms of amiodarone neurotoxicity. Our study shows that predicting effects from in vitro data together with IVIVE can be used at the initial stage for the evaluation of potential adverse drug reactions and safety assessment in humans.

Long-term simulation of lead concentrations in agricultural soils in relation to human adverse health effects - Thomas Schupp; Georg Damm; Heidi Foth; Alexius Freyberger; Thomas Gebel; Ursula Gundert-Remy; Jan G. Hengstler; Aswin Mangerich; Falko Partosch; Claudia Röhl; Klaus-Michael Wollin (Archives of Toxicology, 2020)
Lead (Pb) exposure of consumers and the environment has been reduced over the past decades. Despite all measures taken, immission of Pb onto agricultural soils still occurs, with fertilizer application, lead shot from hunting activities, and Pb from air deposition representing major sources. Little is known about the intermediate and long-term consequences of these emissions. To gain more insight, we established a mathematical model that considers input from fertilizer, ammunition, deposition from air, uptake of Pb by crops, and wash-out to simulate the resulting Pb concentrations in soil over extended periods. In a further step, human oral exposure by crop-based food was simulated and blood concentrations were derived to estimate the margin of exposure to Pb-induced toxic effects. Simulating current farming scenarios, a new equilibrium concentration of Pb in soil would be established after several centuries. Developmental neurotoxicity represents the most critical toxicological effect of Pb for humans. According to our model, a Pb concentration of ~ 5 mg/kg in agricultural soil leads to an intake of approximately 10 µg Pb per person per day by the consumption of agricultural products, the dose corresponding to the tolerable daily intake (TDI). Therefore, 5 mg Pb/kg represents a critical concentration in soil that should not be exceeded. Starting with a soil concentration of 0.1 mg/kg, the current control level for crop fields, our simulation predicts periods of ~ 50 and ~ 175 years for two Pb immission scenarios for mass of Pb per area and year [scenario 1: ~ 400 g Pb/(ha × a); scenario 2: ~ 175 g Pb/(ha × a)], until the critical concentration of ~ 5 mg/kg Pb in soil would be reached. The two scenarios, which differ in their Pb input via fertilizer, represent relatively high but not unrealistic Pb immissions. From these scenarios, we calculated that the annual deposition of Pb onto soil should remain below ~ 100 g/(ha × a) in order not to exceed the critical soil level of 5 mg/kg. We propose as efficient measures to reduce Pb input into agricultural soil to lower the Pb content of compost and to use alternatives to Pb ammunition for hunting.

Translational toxicology of sex specific PFNA clearance in rat and human - Christoph Hethey; Hans Mielke; Ursula Gundert-Remy (Archives of Toxicology, 2020)

Prediction of human drug-induced liver injury (DILI) in relation to oral doses and blood concentrations - Wiebke Albrecht; Franziska Kappenberg; Tim Brecklinghaus; Regina Stoeber; Rosemarie Marchan; Mian Zhang; Kristina Ebbert; Hendrik Kirschner; Marianna Grinberg; Marcel Leist; Wolfgang Moritz; Cristina Cadenas; et al. (Archives of Toxicology, 2019)

Comment on ‘Kim, S.-J., Choi, E.-J., Choi, G.-W., Lee, Y.-B., and Cho, H.-Y. (2019). Exploring sex differences in human health risk assessment for PFNA and PFDA using a PBPK model, Arch Toxicol 93:311–330’ - Christoph Hethey; Hans Mielke; Ursula Gundert-Remy (Archives of Toxicology, 2019)

Importance of in vitro conditions for modeling the in vivo dose in humans by in vitro–in vivo extrapolation (IVIVE) - Engi Abdel Hady Algharably; Reinhold Kreutz; Ursula Gundert-Remy (Archives of Toxicology, 2019)

In vitro proteomic analysis of methapyrilene toxicity in rat hepatocytes reveals effects on intermediary metabolism - Albert Braeuning; Axel Oberemm; Tanja Heise; Ursula Gundert-Remy; Jan G. Hengstler; Alfonso Lampen (Archives of Toxicology, 2019)

Comparative risks of bleeding, ischemic stroke and mortality with direct oral anticoagulants versus phenprocoumon in patients with atrial fibrillation - Mariam Ujeyl; Ingrid Köster; Hans Wille; Thomas Stammschulte; Rebecca Hein; Sebastian Harder; Ursula Gundert-Remy; Julian Bleek; Peter Ihle; Helmut Schröder; Gerhard Schillinger; Anette Zawinell; et al. (European Journal of Clinical Pharmacology, 2018)

High exposure to inorganic arsenic by food: the need for risk reduction - Ursula Gundert-Remy; Georg Damm; Heidi Foth; Alexius Freyberger; Thomas Gebel; Klaus Golka; Claudia Röhl; Thomas Schupp; Klaus-Michael Wollin; Jan Georg Hengstler (Archives of Toxicology, 2015)

Metamizole (dipyrone)-associated agranulocytosis. An analysis of German spontaneous reports 1990–2012 - Thomas Stammschulte; Wolf-Dieter Ludwig; Bernd Mühlbauer; Elisabeth Bronder; Ursula Gundert-Remy (European Journal of Clinical Pharmacology, 2015)

Internal threshold of toxicological concern values: enabling route-to-route extrapolation - Falko Partosch; Hans Mielke; Ralf Stahlmann; Burkhard Kleuser; Susan Barlow; Ursula Gundert-Remy (Archives of Toxicology, 2015)

Sensory irritation as a basis for setting occupational exposure limits - Thomas Brüning; Rüdiger Bartsch; Hermann Maximillian Bolt; Herbert Desel; Hans Drexler; Ursula Gundert-Remy; Andrea Hartwig; Rudolf Jäckh; Edgar Leibold; Dirk Pallapies; Albert W. Rettenmeier; Gerhard Schlüter; et al. (Archives of Toxicology, 2014)

Functional UDP-glucuronyltransferase 2B15 polymorphism and bisphenol A concentrations in blood: results from physiologically based kinetic modelling - Falko Partosch; Hans Mielke; Ursula Gundert-Remy (Archives of Toxicology, 2013)

Pharmacokinetics explain in vivo/in vitro discrepancies of carcinogen-induced gene expression alterations in rat liver and cultivated hepatocytes - Markus Schug; Regina Stöber; Tanja Heise; Hans Mielke; Ursula Gundert-Remy; Patricio Godoy; Raymond Reif; Meinolf Blaszkewicz; Heidrun Ellinger-Ziegelbauer; Hans-Jürgen Ahr; Silvia Selinski; Georgia Günther; et al. (Archives of Toxicology, 2013)

A physiologically based toxicokinetic modelling approach to predict relevant concentrations for in vitro testing - Hans Mielke; Lennart T. Anger; Markus Schug; Jan G. Hengstler; Ralf Stahlmann; Ursula Gundert-Remy (Archives of Toxicology, 2011)

Alternative (non-animal) methods for cosmetics testing: current status and future prospects—2010 - Sarah Adler; David Basketter; Stuart Creton; Olavi Pelkonen; Jan van Benthem; Valérie Zuang; Klaus Ejner Andersen; Alexandre Angers-Loustau; Aynur Aptula; Anna Bal-Price; Emilio Benfenati; Ulrike Bernauer; et al. (Archives of Toxicology, 2011)

Chronic oral LOAEL prediction by using a commercially available computational QSAR tool - Bernd Rupp; Klaus E. Appel; Ursula Gundert-Remy (Archives of Toxicology, 2010)

Letter to the Editor: A regulatory view on the discussion on the role of alternative methods in the risk assessment of chemicals in the context of REACH - Ursula Gundert-Remy; Ulrike Bernauer; Stephan Madle; Axel Oberemm; Agnes Schulte; Hans-Bernhard Richter-Reichhelm (Archives of Toxicology, 2009)

Human CYP2E1 mediates the formation of glycidamide from acrylamide - Eva Settels; Ulrike Bernauer; Richard Palavinskas; Horst S. Klaffke; Ursula Gundert-Remy; Klaus E. Appel (Archives of Toxicology, 2008)

Elevated internal exposure of children in simulated acute inhalation of volatile organic compounds: effects of concentration and duration - Klaus Abraham; Hans Mielke; Wilhelm Huisinga; Ursula Gundert-Remy (Archives of Toxicology, 2005)

Animal testing and alternative approaches for the human health risk assessment under the proposed new European chemicals regulation - Thomas Hfer; Ingrid Gerner; Ursula Gundert-Remy; Manfred Liebsch; Agnes Schulte; Horst Spielmann; Richard Vogel; Klaus Wettig (Archives of Toxicology, 2004)

In vitro prediction of gastrointestinal absorption and bioavailability: an experts' meeting report - Olavi Pelkonen; Alan R. Boobis; Ursula Gundert-Remy (European Journal of Clinical Pharmacology, 2001)

CYP2E1 expression in bone marrow and its intra- and interspecies variability: approaches for a more reliable extrapolation from one species to another in the risk assessment of chemicals - Ulrike Bernauer; Bärbel Vieth; Rainer Ellrich; Barbara Heinrich-Hirsch; Gerd-Rüdiger Jänig; Ursula Gundert-Remy (Archives of Toxicology, 2000)

CYP2E1-dependent benzene toxicity: the role of extrahepatic benzene metabolism - Ulrike Bernauer; Bärbel Vieth; Rainer Ellrich; Barbara Heinrich-Hirsch; Gerd-Rüdiger Jänig; Ursula Gundert-Remy (Archives of Toxicology, 1999)

Modelling of residual variability in toxicokinetic studies with sparse sampling: the case of tetrahydronaphthalene - Ingolf Meineke; Johanna Eisele; Hans Certa; Ursula M. Gundert-Remy (Archives of Toxicology, 1998)